AN ANALYSIS OF SUBTITLING STRATEGIES USED IN THE EXPRESSIVE UTTERANCES IN THE ‘THE FATHER’ MOVIE - Marcella Pricilia; Nurlaila Nurlaila (Universitas Gunadarma, 2022)
This research discusses subtitling strategies for expressive utterances of a movie entitled ‘The Father’ from English into Indonesian. The objectives of this research are to identify types of expressive utterances and to investigate subtitle strategies used in translating the expressive utterances of the main character in ‘The Father’ movie. The researcher uses the qualitative method. The sources of the data are English and Indonesian original subtitles of ‘The Father’ movie. The data of this research ar e expressive utterances produced by the main character in ‘The Father’ movie. The results show that there are six types of expressive utterances in ‘The Father’ movie, including boasting (22), deploring (20), lamenting (15), thanking (6), apologizing (5), and forgiving (1). Besides that, there are eight subtitling strategies are used, including transfer (40), paraphrase (25), condensation (4), expansion (3), deletion (2), imitation (2), decimation (1), and transcription (1). Based on the results of the analysis, the most dominant type of expressive utterances used in the movie is Boasting (32%) and the subtitling strategy frequently used is Transfer (51%).